Notes on coherent polarization X-ray radiation by relativistic electrons in a crystal - Morokhovskii, V.L. (Вопросы атомной науки и техники, 2019)
This paper deals with restrictions on the use of so-called kinematical theory of coherent polarization X-ray radiation by relativistic electrons in a single crystal target.